2014
DOI: 10.1111/hel.12179
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter cinaedi Induced Typhlocolitis in Rag‐2‐Deficient Mice

Abstract: Background Helicobacter cinaedi, an enterohepatic helicobacter species (EHS), is an important human pathogen and is associated with a wide range of diseases, especially in immunocompromised patients. It has been convincingly demonstrated that innate immune response to certain pathogenic enteric bacteria is sufficient to initiate colitis and colon carcinogenesis in recombinase-activating gene (Rag)-2-deficient mice model. To better understand the mechanisms of human IBD and its association with development of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…and 67% of the infected mice developed GIN with dysplasia score above 3. There were no correlations with helicobacter colonization levels and the severity of pathology in H.japonicum infected IL10 −/− mice which is consistent with other EHS-induced intestinal disease in mouse models (22,25).…”
Section: Discussionsupporting
confidence: 85%
“…and 67% of the infected mice developed GIN with dysplasia score above 3. There were no correlations with helicobacter colonization levels and the severity of pathology in H.japonicum infected IL10 −/− mice which is consistent with other EHS-induced intestinal disease in mouse models (22,25).…”
Section: Discussionsupporting
confidence: 85%
“…and different than H. suis; however, our 16S rRNA sequence analysis demonstrating 95% homology to H. pullorum supports this possibility. We have recently reported that another enterohepatic helicobacter, H. cinaedi, persistently colonizes the stomach of mice [42]. This finding also emphasizes previous studies where H. cinaedi was identified in the stomachs of humans, some with gastric cancer [43,44].…”
Section: Discussionsupporting
confidence: 84%
“…EHS infection exacerbates the onset of disease in IL-10 Ϫ/Ϫ mice and thus is a frequently used model to study pathogen-induced IBD and colon cancer. H. hepaticus and H. bilis are the most thoroughly studied EHS; however, other EHS, like H. trogontum, H. typhlonius, H. rodentium, H. mastomyrinus, and H. cinaedi, a human pathogen, can also cause IBD-like disease in immunocompromised mice (9,11,34,(38)(39)(40). Because EHS-induced colitis in IL-10 Ϫ/Ϫ mice is well characterized, we chose this mouse model to investigate the pathogenic potential of H. saguini.…”
Section: Discussionmentioning
confidence: 99%